2019
DOI: 10.7717/peerj.7478
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of bacteria isolated from the stingless bee,Heterotrigona itama, honey, bee bread and propolis

Abstract: Bacteria are present in stingless bee nest products. However, detailed information on their characteristics is scarce. Thus, this study aims to investigate the characteristics of bacterial species isolated from Malaysian stingless bee, Heterotrigona itama, nest products. Honey, bee bread and propolis were collected aseptically from four geographical localities of Malaysia. Total plate count (TPC), bacterial identification, phenotypic profile and enzymatic and antibacterial activities were studied. The results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
55
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(72 citation statements)
references
References 53 publications
6
55
0
1
Order By: Relevance
“…The amount of aerobic bacteria detected in the fresh honey of stingless bees could be considered relatively low, with a mean value of 1.7 x 10 2 CFU/g, compared to its other byproducts, such as beebread and propolis (1.83 × 10 6 CFU/g) [12,37]. This is supported by the results from a previous study, as the presence of aerobic bacteria in honey was also detected in the range of 5.7 × 10 0 to 52.8 × 10 4 CFU/g [38].…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…The amount of aerobic bacteria detected in the fresh honey of stingless bees could be considered relatively low, with a mean value of 1.7 x 10 2 CFU/g, compared to its other byproducts, such as beebread and propolis (1.83 × 10 6 CFU/g) [12,37]. This is supported by the results from a previous study, as the presence of aerobic bacteria in honey was also detected in the range of 5.7 × 10 0 to 52.8 × 10 4 CFU/g [38].…”
Section: Discussionmentioning
confidence: 95%
“…A recent study found that the highest microbial diversity was found in multifloral honey [13]. Recently, the presence of B. altitudinis in stingless bee honey, H. itama, was reported for the first time [12]. B. altitudinis had been previously found in Apis mellifera honey together with other Bacillus isolates, namely B. licheniformis, B. safensis, B. zhangzhouensis, and B. xiamenensis [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of researchers confirmed that they had found that in honey microbiota and honey bag of bee there were bacterial strains with the high level of antimicrobial activity against pathogens which were resistant to antibiotics. This reveals antimicrobial properties of honey [10][11].…”
Section: Literature Reviewmentioning
confidence: 59%
“…B. amyloliquefaciens strains are capable of producing different bioactive compounds useful in bio-control of plant and human pathogens (Balhara et al, 2011). This bacterial species is widely distributed in various niches including soil (Lončar et al, 2013), foods (Krawczyk et al, 2016), fruits (Wu et al, 2017), bee products (Ngalimat et al, 2019), animal faeces (Singh et al, 2013), and aquatic environments (Daas et al, 2018).…”
mentioning
confidence: 99%